Bürgerinvestitionen in die Energiewende. [Themenheft] - (:unkn) unknown (Steiner, 2012)
Nur ein starker Ausbau erneuerbarer Energien kann die Energieversorgung in Deutschland in die beschlossene Richtung wenden. Unweigerlich wird damit die sog. Fläche mehr und mehr zum Standort der Energieproduktion und neuer Energieinfrastrukturen. Wie kann die Akzeptanz der Bevölkerung vor Ort dafür gewonnen werden? Regionale Organisation der Energieproduktion, Mitsprache sowie wirtschaftliche Beteiligungsmöglichkeiten der Bürger und regionale Wertschöpfung könnten die Antwort auf diese Frage sein und werden auch schon erfolgreich praktiziert - wie in diesem Heft gezeigt wird.

The energy turn requires a fundamental reorganisation of the energy system, which creates economic, technological and organisational challenges for Germany. A core element of the energy turn is the development of renewable energies. The ambitious development goals of the Federal Government require the broadest and most rapid use of all the potentials of renewable energies in Germany that is possible. In addition to the implementation of capital-intensive large projects such as offshore wind parks, the use of decentralised, regional production potentials is of great importance. Therefore rural regions play a fundamental role in the development of renewable energies. Economic development potentials result for rural regions from the energy turn if it is possible to invest regional capital directly and locally in renewable energies. With regard to Germany as a whole, the energy turn will lead to energy production through relocation, but also to regional economic redistribution effects with benefiting and losing regions. The more strongly the energy turn is based on decentralised facilities for the production of renewable energies, the more strongly the structure of actors on the energy market will be diversified. The change in the structure of actors is expressed most clearly in the great significance of civic investments in the current phase of the energy turn. Civic investments in their different forms of organisation such as civic energy cooperative societies or climate saving bonds are of central importance for a successful modernisation of the energy production in Germany for two reasons: Firstly, only the direct (also financial) participation of the people whose direct living and housing environment is influenced by the new facilities is able to create the necessary acceptance for the concrete implementation of the energy turn in Germany. Secondly, the production of renewable energy in rural regions can contribute to the strengthening of the local economy and thus create an additional positive economic impulse for the energy turn.
Energy turn, civic investments and regional development.
Keywords: Energie; Alternativenergie; Energiepolitik; Energieversorgung; Energieproduktion; Energiewirtschaft; Energiewende; Erneuerbare Energie; Bürgerbeteiligung; Beteiligungsmodell